Imatinib and pegylated IFN‐α2b discontinuation in first‐line chronic myeloid leukemia patients following a major molecular response. (28th January 2014) - Koskenvesa, Perttu; Kreutzman, Anna; Rohon, Peter; Pihlman, Markus; Vakkila, Emmi; Räsänen, Anu; Vapaatalo, Mirja; Remes, Kari; Lundán, Tuija; Hjorth‐Hansen, Henrik; Vakkila, Jukka; Simonsson, Bengt; et al.
Abstract Objectives Previous studies indicate that 40–50% of patients with chronic myeloid leukemia in prolonged complete molecular remission may discontinue imatinib therapy without imminent relapse. The combination of pegylated interferon‐alpha (Peg‐IFN‐α2b) and imatinib may increase the rate of successful discontinuation. Methods In this pilot study, we prospectively stopped imatinib from patients (n = 12) who had achieved major molecular response (MMR) after ≥12 months of treatment with either imatinib or imatinib+Peg‐IFN‐α2b. Molecular monitoring was carried out monthly for BCR‐ABL1. In addition, analyses of lymphocyte immunophenotype, function, and plasma cytokines were performed. Results In the monotherapy group, 5/6 patients lost MMR within 4 months. One patient remains to date in MR4.0 61 months after discontinuation. In the combination therapy group, 2/6 patients relapsed within 4 months while still receiving Peg‐IFN‐α2b. Four of six patients were able to discontinue both treatments, but three of these patients relapsed after 3 months. One patient is still in sustained MR4.0 at 58 months off all treatment. All relapsed patients re‐responded to imatinib. The two successfully discontinued patients had either an increased number of NK‐cells or functionally active T‐cells. Conclusions A higher frequency of relapsed patients in our study in comparison with other studies may be due to the shorter duration of imatinib treatment prior to discontinuation. However, in selected patients with an active immune system, even a short duration of TKI therapy (<2 yr) may allow for therapy discontinuation but this needs to be confirmed in larger prospective studies.